Comparison of Induced Chlorophyll mutations and Spectrum in Two Varieties of Trigonella foenum- graecum L. - Zia-Ul-Hasan, Dheeraj Vasu* and (Journal of Phytology, 2011)
The present study was carried out to compare the induced chlorophyll mutations and spectrum in two varieties of Trigonella foenum-graecum L. viz., desi and kasuri methi. It was observed that the highest chlorophyll mutation frequency was obtained with 0.3% MES & highest chlorophyll spectrum with 0.3% MMS in desi methi. The highest chlorophyll mutation frequency was obtained with 0.3% EMS & chlorophyll mutation spectrum with MMS in kasuri methi, but the mutation spectrum was broader in desi methi as compared to kasuri methi. Key words: Mutation, EMS, MMS, MES, Trigonella foenum-graecum L. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Dheeraj Vasu and Zia-Ul-Hasan. Comparison of Induced Chlorophyll mutations and Spectrum in Two Varieties of Trigonella foenum- graecum L.. J Phytol 3/3 (2011) 37-43